Sustentabilidade hidroambiental de nascentes na bacia hidrográfica do rio Gramame no Estado da Paraíba, Brasil / Hydro-Environmental Sustainability of the Gramame river basin headwaters in Paraiba State, Brazil - Eudes de Oliveira Bomfim; Carmem Lúcia Moreira Gadelha; Hamilcar José Almeida Filgueira; Jamille Freire Amorim; Diego da Silva Amorim (Sociedade & Natureza)
This study has aimed to determine the level of hydro-environmental sustainability of areas surrounding headwaters in the Gramame river basin, located in Pedras de Fogo county, Paraíba State. Four headwaters were chosen for the development of this research: Cacimba da Rosa and Cabelão, in the intermediate rural-urban zone; Nova Aurora and Fazendinha, in the countryside. The methodology used to obtain the sustainability index was based on the work of the Calorie (1997) and Daniel (2001). It was used the radar chart type, by which it was possible to dynamically compare all variables. The largest area of the triangle formed on the chart, is the largest sustainability indicator. The final indices revealed that the area around the Nova Aurora headwaters got the best performances of their indicators.